Book review: Zadra, A., & Stickgold, R. (2021). When brains dream: exploring the science and mystery of sleep - Schredl, Michael (International journal of dream research, 2021)
The book is full of personal anecdotes and examples of empirical studies the authors carried out; this is fun to read and illustrates the enthusiasm of both authors regarding dreams. The book is also full of useful information, starting from a brief overview regarding the history of dreams research to current research topics like lucid dreaming, nightmares, and sleep-dependent memory consolidation. The authors propose a framework called “Network exploration to understand possibilities” (NEXTUP) indicating possible function(s) of dreaming, the conscious experiencing during sleep that might be different from the functions of sleep per se. Although, some aspects of the model seem plausible and are based on previously formulated hypotheses about dream function, the major caveat is the testability of functions of unremembered dreams. Based on the findings so far, my bet would not be to focus on weak and previously unexplored associations for explaining how dreams relate to waking-life issues but pursue the idea that dreams are straight-forward depictions of waking-life emotions and basic behavioral patterns using graphic, dramatic metaphors to make sure the dreamer understands the importance.
Gesehen am 23.04.2021
Keywords: Rezension